The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/s0140-6736(15)00548-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in patients with ST-segment elevation myocardial infarction treated with everolimus-eluting stents versus bare-metal stents (EXAMINATION): 5-year results of a randomised trial

Abstract: SummaryBackground Data for the safety and effi cacy of new-generation drug-eluting stents at long-term follow-up, and specifi cally in patients with ST-segment elevation myocardial infarction, are scarce. In the EXAMINATION trial, we compared everolimus-eluting stents (EES) with bare-metal stents (BMS) in an all-comer population with ST-segment elevation myocardial infarction. In this study, we assessed the 5-year outcomes of the population in the EXAMINATION trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(115 citation statements)
references
References 35 publications
(45 reference statements)
7
97
3
5
Order By: Relevance
“…In this study EES also significantly reduced the rates of target-lesion revascularization (7). Moreover, the 5-year results of this randomized trial (8) confirmed that the sustained clinical efficacy of EES in STEMI patients may translate into a survival improvement.…”
Section: Introductionsupporting
confidence: 75%
“…In this study EES also significantly reduced the rates of target-lesion revascularization (7). Moreover, the 5-year results of this randomized trial (8) confirmed that the sustained clinical efficacy of EES in STEMI patients may translate into a survival improvement.…”
Section: Introductionsupporting
confidence: 75%
“…In patients with STEMI, DES (in particular new-generation DES) have demonstrated better efficacy as compared with BMS and should be used as the default strategy in STEMI patients, even when DAPT cannot be sustained beyond 1 month. 177,178,[216][217][218] (see section 16.1.2). As discussed in section 16.4, radial access is preferred over femoral access.…”
Section: Primary Percutaneous Coronary Interventionmentioning
confidence: 99%
“…In addition, increasing age was associated with BMS use in the present trial which is also seen elsewhere in the literature. The age-dependent selection of stent type is probably reasoned by the results of the COMFORTABLE AMI and EXAMINATION trial which did not show superiority of DES over BMS in patients>65 years19 and >75 years,3 respectively. Single vessel disease predicting BMS use in the present analysis is probably explainable by the higher risk for restenosis with BMS 3 19.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly based on the long-term data of the Comparison of Biolimus Eluted From an Erodible Stent Coating With Bare Metal Stents in Acute ST-Elevation Myocardial Infarction (COMFORTABLE AMI)2 and Everolimus-Eluting Stents Versus Bare-Metal Stents in ST-Segment Elevation Myocardial Infarction (EXAMINATION) trials,3 current European guidelines recommend the use of drug-eluting stents (DES) over bare-metal stents (BMS) in AMI regardless of presentation with ST-elevation or non-ST-elevation infarction 4. In contrast, current US guidelines do not recommend a preference for DES in AMI 5 6…”
Section: Introductionmentioning
confidence: 99%